Contagion of offensive speech online: An interactional analysis of political swearing. (February 2022) - Song, Yunya; Lin, Qinyun; Kwon, K. Hazel; Choy, Christine H.Y.; Xu, Ran
Abstract: Despite their positive effects in promoting participatory politics, digital publics have also manifested an offensive vernacular culture. This study takes a social network analytic approach to explain the contagion of offensive speech in online discussion contexts. The study examines four social interactional mechanisms underlying a user's adoption of political swearing: generalized reciprocity, direct reciprocity, leader-mimicry, and peer-mimicry. The empirical context of this study is a highly popular online discussion forum in Hong Kong. The study examines the effects of social interactional mechanisms on the occurrences of political swearing by analyzing five years of user comments. Findings show that peer-mimicry contributes to the contagion process the most, followed by generalized reciprocity and direct mimicry. The study demonstrates how individual-level speech behaviors spiral into a collective norm that potentially hinders a healthy discussion culture in mediated social spaces. Highlights: This study explained the contagion of offensive speech in online discussion. We analyzed large-scale datasets collected from a popular discussion forum. Various social interactional mechanisms (e.g., reciprocity and mimicry) were examined. We illustrated how individual-level offensive speech spirals into a toxic vernacular culture online.